2017
DOI: 10.1186/s12885-017-3674-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-17-5p suppresses cell proliferation and invasion by targeting ETV1 in triple-negative breast cancer

Abstract: BackgroundTriple-negative breast cancer (TNBC) is the malignancy with the worst outcome among all breast cancer subtypes. We reported that ETV1 is a significant oncogene in TNBC tumourigenesis. Consequently, investigating the critical regulatory microRNAs (miRNAs) of ETV1 may be beneficial for TNBC targeted therapy.MethodsWe performed in situ hybridization (ISH) and immunohistochemistry (IHC) to detect the location of miR-17-5p and ETV1 in TNBC patient samples, respectively. miR-17-5p expression in TNBC tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 34 publications
2
55
0
Order By: Relevance
“…In the ES model, we analyzed 14 AS events related to the prognosis of GBC, including ETV1, SH2D4A, BCLAF1, and SUV420H1. One breast cancer study indicated that cell proliferation and invasion in triple-negative breast cancer can be suppressed through miR-17-5p targeting ETV1, and ETV1 was proven to be a significant oncogene in triple-negative breast cancer [53]. This is also consistent with our findings; the overexpression of ETV1 is associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…In the ES model, we analyzed 14 AS events related to the prognosis of GBC, including ETV1, SH2D4A, BCLAF1, and SUV420H1. One breast cancer study indicated that cell proliferation and invasion in triple-negative breast cancer can be suppressed through miR-17-5p targeting ETV1, and ETV1 was proven to be a significant oncogene in triple-negative breast cancer [53]. This is also consistent with our findings; the overexpression of ETV1 is associated with poor prognosis.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, miR-1297, miR-143-3p, miR-503 and miR-205 also promote LSCC cell progression [14][15][16][17]. Recent studies have confirmed that miR-17-5p plays critical roles in tumor progression, such as pancreatic cancer, breast cancer, hepatocellular carcinoma, gastric cancer and prostate cancer [18][19][20][21][22]. However, the expression and biological functions of miR-17-5p in LSCC remain unclear.…”
mentioning
confidence: 99%
“…We further analyzed whether any of the highly expressed miRNAs were previously associated with TNBC and found that seven out of the 83 miRNAs, common for all three cell lines (miR-181b-5p, miR-221-3p, miR-27a-3p, miR-21-3p, miR-20a-5p, miR-103a-3p and miR-25-3p), have been previously associated with the TNBC phenotype [39][40][41][42][43][44][45][46][47] Another three molecules, miR-210-3p, miR-155-5p and miR-125b-5p, highly expressed in HCC1806 and Hs 578T cells, are known as hallmarks of TNBC [40,41,48,49], whereas miR-342-3p, highly expressed exclusively in basal-like TNBC cell lines, has been previously described as an important regulator of molecular mechanisms of this breast cancer subtype [50]. Interestingly, miRNAs miR-101-3p, miR-17-5p, miR-93-5p, miR-340-5p, and miR-31-5p, known mainly for their tumor suppressor properties, were found among the top expressed miRNAs in our dataset [51][52][53][54][55][56][57][58]. Finally, three miRNAs whose role is contradictory according to the literature (miR-181a-5p, miR-182-5p, and miR-26a-5p) were found to be highly expressed in all three cell lines analyzed [39,[59][60][61][62][63][64][65][66][67][68].…”
Section: Characterization Of Small Non-coding Rna Expression Profile mentioning
confidence: 56%